SISTEM INFORMASI PENDAFTARAN SISWA BARU BERBASIS WEB UNTUK SEKOLAH YAYASAN AL-MADRASATUL MAHDALIYAH JAMBI - Yeni Nurjani; Eza Dwi Satria; Mulyadi Mulyadi (LP2M Universitas Nurdin Hamzah, 2026)
In today's digital era, technology-based administrative systems are essential to enhance the efficiency and effectiveness of data management in the education sector. Madrasah Tsanawiyah Al-Madrasatul Mahdaliyah Jambi still uses a manual student registration system, which often results in issues such as data entry errors, duplication, and delays in processing information. Therefore, this study aims to design and develop a web-based student administration information system using the CodeIgniter framework and MySQL database. This system is designed to facilitate the new student registration process, improve data accuracy, and provide easy access for students and school administrators in managing registration information. The results of this study indicate that the developed system improves administrative efficiency, reduces recording errors, and accelerates information access. Thus, the implementation of this system can be a solution to optimize student administration management at Madrasah Tsanawiyah Al-Madrasatul Mahdaliyah Jambi.